A high-strength CoCrFeNi high-entropy alloy containing Gd and V and a preparation method thereof
By adding V elements and adjusting the GD content in the Cocrfeni tie high entropy alloys, the vacuum sensor melting legal system prepares a high -intensity GDXCOCRFENIV0.4 high entropy alloy to solve the problem of low room temperature and achieve high intensity and good mechanics performance.
Patent Information
- Application Number
- CN202410476565.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-04-19
AI Technical Summary
The low room temperature strength of CoCrFeNi-based high-entropy alloys limits its application as a structural material.
By adding an appropriate amount of V element and adjusting the amount of Gd element, GdxCoCrFeNiV0.4 high-entropy alloy was prepared using vacuum induction melting method to refine the grains, solid solution strengthen and improve the hardness and tensile strength of the alloy.
It significantly improves the intensity of high entropy alloys. The yield strength is maintained above 1300MPa. The compression strain is 9 % to 10 %, the hardness is higher than 600HV, and the average grain size drops to 25.67 μm.
Smart Images

Figure CN118374723B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high entropy alloy materials, and in particular to a high-strength CoCrFeNi high entropy alloy containing Gd and V and a preparation method thereof. Background Art
[0002] High entropy alloys (HEAs) have attracted increasing attention in metal materials for their unique properties and broader design possibilities. The concept of HEAs is based on the idea that high mixing entropy promotes the formation of stable single-phase structures. It is a new type of material that has attracted much attention in recent years. They are multi-principal element alloys, which are composed of four or more main elements to form a simple solid solution phase and have good prospects in structural applications. In the past few years, various alloy systems have been explored to identify HEA systems with improved performance combinations, leading to extraordinary developments in this field. So far, there are currently three main representative categories of HEAs discovered by people: Cantor alloys, Senkov alloys, and low-density high-entropy alloys. The concept of high-entropy alloys has created a huge, global driving force for alloy design, which is unprecedented in the history of materials and metallurgical research. Combined with the current research status at home and abroad, the preparation methods of high-entropy alloys include vacuum melting, mechanical alloying, magnetron sputtering, electrochemical method, laser additive manufacturing, etc. Vacuum melting methods are divided into vacuum arc melting and vacuum induction melting. Compared with vacuum arc melting, vacuum induction melting is easier to control temperature, but it strengthens the scouring of the melt on the furnace lining, increases the erosion intensity, and makes the alloy characteristics unstable. Residual stress and segregation are prone to occur during the preparation process; the mechanical alloying preparation process is simple and easy to achieve alloying. However, residual stress will be generated during the grinding process, and diffusion will occur, resulting in defects such as oxidation inside the alloy; the controlled sputtering method can accurately control the film thickness, improve corrosion resistance, and improve the mechanical properties and phase structure of high entropy alloy films. However, it is only suitable for making thin films and has limitations; the electrochemical deposition method can freely control the film thickness and has little pollution to the environment. However, because stress cannot be avoided, defects in the film structure may affect the corrosion behavior of long-term immersion in such a corrosive electrolyte; the alloy prepared by the laser cladding method has good thermal stability, uniform chemical composition, excellent mechanical properties, and relatively high surface accuracy and density. However, residual stress will also be generated, leading to cracks.
[0003] CoCrFeNi high entropy alloys have excellent properties, but low room temperature strength. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of low room temperature strength of existing CoCrFeNi series high entropy alloys, which limits their application as structural materials, and to provide a high-strength CoCrFeNi high entropy alloy containing Gd and V and a preparation method thereof.
[0005] The invention solves the problem of low room temperature strength of CoCrFeNi series high entropy alloys. By adding a proper amount of V element, it helps to refine grains, strengthen solid solution and reduce the segregation of Cr element in the alloy. Moreover, the V element can improve the hardness and tensile strength of the high entropy alloy without changing the phase structure of the CoCrFeNi alloy. The strength of the high entropy alloy is improved by regulating the addition amount of the Gd element.
[0006] A high-strength CoCrFeNi high-entropy alloy containing Gd and V comprises the following components by weight percentage: V:
[0007] 8.34% to 9.08%, Co: 20.83% to 22.73%, Cr: 20.83% to 22.73%, Fe: 20.83% to 22.73%, Ni: 20.83% to 22.73%, Gd: 2.23% to 8.34%.
[0008] A method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V is specifically completed by the following steps:
[0009] 1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.34% to 9.08%, Co: 20.83% to 22.73%, Cr: 20.83% to 22.73%, Fe: 20.83% to 22.73%, Ni: 20.83% to 22.73%, and Gd: 2.23% to 8.34% to obtain a raw material;
[0010] 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0011] 3. Melting:
[0012] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min-10min, then adjust to 150kW, melt at 150kW for 5min-10min, then adjust to 200kW, melt at 200kW for 5min-10min, finally adjust to 150kW, melt at 150kW for 10min-15min, and cool down to 100℃-150℃ with the furnace;
[0013] ② Repeat step 3① 3 to 4 times, turning the material up and down between two smeltings, and pouring after smelting to obtain a high-strength CoCrFeNi high-entropy alloy containing Gd and V.
[0014] Principle of the present invention:
[0015] Vacuum induction melting refers to placing high entropy alloy raw materials and induction coils in a vacuum and sealed container. Under the action of current, the induction coil generates electromotive force to generate eddy currents inside the material and generate a large amount of heat, melting the high entropy alloy raw materials and casting them into shape. In the present invention, Gd is prepared by adding an appropriate amount of V element and adjusting the Gd element content using a vacuum suspension melting furnace. x CoCrFeNiV 0.4 The microstructure of high entropy alloys (x = 0, 0.1, 0.2, 0.3, 0.4) was observed by Phenom Pro G6 scanning electron microscope (SEM). The hardness was measured by HUAYIN HV-1000A Vickers hardness tester, and the average value was taken for ten measurements in each group to ensure the accuracy of the data. The hardness of each group was measured by INSTRON 68TM-50 tester at a strain rate of 10 -4 s -1 Compression tests were carried out under experimental conditions, and the microstructure of the alloy was characterized by electron backscatter diffraction (EBSD); the corrosion performance of the alloy was tested by electrochemical corrosion test. Finally, it was concluded that Gd 0.3 CoFeNiV 0.4 The alloy has the best comprehensive performance.
[0016] Advantages of the present invention:
[0017] 1. The present invention adopts vacuum induction melting. By adding an appropriate amount of V element to the CoCrFeNi alloy, the grains can be refined to form a single-phase FCC solid solution. The single-phase FCC has high ductility, but the hardness and yield strength are not as expected. By adding V element to the CoCrFeNiV 0.4 Adding rare earth element Gd to high entropy alloy can make the alloy form FCC+Laves two-phase solid solution. The Gd content has a significant effect on the microstructural evolution inside the high entropy alloy, thereby improving the strength of the high entropy alloy.
[0018] 2. Gd with high compression performance prepared by the present invention 0.3 CoFeNiV 0.4 The yield strength of the high-entropy alloy remains above 1300 MPa, and the compressive strain is maintained at 9% to 10%, the hardness is higher than 600 HV, and the average grain size is reduced to 25.67 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM scan of the Gd0.3 high entropy alloy prepared in Example 1;
[0020] Figure 2 Compression curve of the Gd0.3 high entropy alloy prepared in Example 1;
[0021] Figure 3This is the IPF diagram of the Gd0.3 high entropy alloy prepared in Example 1;
[0022] Figure 4 This is a polarization curve diagram of the Gd0.3 high entropy alloy prepared in Example 1;
[0023] Figure 5 Compression curve of the Gd0.4 high entropy alloy prepared in Example 2;
[0024] Figure 6 This is the IPF diagram of the Gd0.4 high entropy alloy prepared in Example 2;
[0025] Figure 7 This is a polarization curve diagram of the Gd0.4 high entropy alloy prepared in Example 2;
[0026] Figure 8 Compression curve of the Gd0.2 high entropy alloy prepared in Example 3;
[0027] Fig. 9 This is the IPF diagram of the Gd0.2 high entropy alloy prepared in Example 3;
[0028] Fig.10 This is a polarization curve diagram of the Gd0.2 high entropy alloy prepared in Example 3;
[0029] Fig.11 Compression curve of the Gd0.1 high entropy alloy prepared in Example 4;
[0030] Fig.12 This is the IPF diagram of the Gd0.1 high entropy alloy prepared in Example 4;
[0031] Fig.13 This is a polarization curve diagram of the Gd0.1 high entropy alloy prepared in Example 4;
[0032] Fig.14 Compression curve of the Gd0 high entropy alloy prepared in Example 5;
[0033] Fig.15 This is the IPF diagram of the Gd0 high entropy alloy prepared in Example 5;
[0034] Fig.16 This is the polarization curve of the Gd0 high entropy alloy prepared in Example 5. DETAILED DESCRIPTION
[0035] Specific implementation method 1: In this implementation method, a high-strength CoCrFeNi high-entropy alloy containing Gd and V includes the following components by weight percentage: V: 8.34% to 9.08%, Co: 20.83% to 22.73%, Cr: 20.83% to 22.73%, Fe: 20.83% to 22.73%, Ni: 20.83% to 22.73%, and Gd: 2.23% to 8.34%.
[0036] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the high-strength CoCrFeNi high-entropy alloy containing Gd and V comprises the following components by weight percentage: V: 8.50%, Co: 21.28%, Cr: 21.28%, Fe: 21.28%, Ni: 21.28%, Gd: 6.38%. The other steps are the same as those of specific embodiment 1.
[0037] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the high-strength CoCrFeNi high-entropy alloy containing Gd and V comprises the following components by weight percentage: V: 8.34%, Co: 20.83%, Cr: 20.83%, Fe: 20.83%, Ni: 20.83%, Gd: 8.34%. The other steps are the same as those of specific embodiment 1 or 2.
[0038] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the high-strength CoCrFeNi high-entropy alloy containing Gd and V comprises the following components by weight percentage: V: 8.70%, Co: 21.74%, Cr: 21.74%, Fe: 21.74%, Ni: 21.74%, Gd: 4.34%. The other steps are the same as those of specific embodiments 1 to 3.
[0039] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the high-strength CoCrFeNi high-entropy alloy containing Gd and V comprises the following components by weight percentage: V: 8.89%, Co: 22.22%, Cr: 22.22%, Fe: 22.22%, Ni: 22.22%, Gd: 2.23%. The other steps are the same as those of specific embodiments 1 to 4.
[0040] Specific implementation method 6: This implementation method is a method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V, which is specifically completed in the following steps:
[0041] 1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.34% to 9.08%, Co: 20.83% to 22.73%, Cr: 20.83% to 22.73%, Fe: 20.83% to 22.73%, Ni: 20.83% to 22.73%, and Gd: 2.23% to 8.34% to obtain a raw material;
[0042] 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0043] 3. Melting:
[0044] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min-10min, then adjust to 150kW, melt at 150kW for 5min-10min, then adjust to 200kW, melt at 200kW for 5min-10min, finally adjust to 150kW, melt at 150kW for 10min-15min, and cool down to 100℃-150℃ with the furnace;
[0045] ② Repeat step 3① 3 to 4 times, turning the material up and down between two smeltings, and pouring after smelting to obtain a high-strength CoCrFeNi high-entropy alloy containing Gd and V.
[0046] Specific implementation method 7: This implementation method is different from specific implementation methods 1 to 6 in that the mass fraction of the hydrochloric acid in step 2 is 5% to 20%. The other steps are the same as those of specific implementation methods 1 to 6.
[0047] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step three ①, under the protection of argon atmosphere, the power of the vacuum suspension melting furnace is first adjusted to 100 kW, and the melting is carried out at 100 kW for 5 min, then adjusted to 150 kW, and the melting is carried out at 150 kW for 5 min, then adjusted to 200 kW, and the melting is carried out at 200 kW for 5 min, and finally adjusted to 150 kW, and the melting is carried out at 150 kW for 15 min, and the temperature is cooled to 100° C. with the furnace. The other steps are the same as those of specific embodiments one to seven.
[0048] Specific implementation method 9: The difference between this implementation method and specific implementation methods 1 to 8 is that step 3 ① is repeated 3 times in step 3 ②. The other steps are the same as those of specific implementation methods 1 to 8.
[0049] The following examples are used to verify the beneficial effects of the present invention:
[0050] Example 1: A method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V is specifically completed by the following steps:
[0051] 1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.50%, Co: 21.28%, Cr: 21.28%, Fe: 21.28%, Ni: 21.28%, and Gd: 6.38% to obtain a raw material;
[0052] 2. Wash the raw materials with 10% hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0053] 3. Melting:
[0054] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min, then adjust to 150kW, melt at 150kW for 5min, then adjust to 200kW, melt at 200kW for 5min, finally adjust to 150kW, melt at 150kW for 15min, and cool down to 100℃ with the furnace;
[0055] ②. Repeat step 3① 3 times. Turn the material upside down between two smeltings. After smelting, pour it to obtain Gd0.3 high entropy alloy, that is, high-strength CoCrFeNi high entropy alloy containing Gd and V.
[0056] Figure 2 Compression curve of the Gd0.3 high entropy alloy prepared in Example 1; Figure 3 This is the IPF diagram of the Gd0.3 high entropy alloy prepared in Example 1. The relevant performance test data are shown in Table 1; Figure 4 This is the polarization curve of the Gd0.3 high entropy alloy prepared in Example 1. The relevant performance test data are shown in Table 2.
[0057] Example 2: A method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V is specifically completed by the following steps:
[0058] 1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.34%, Co: 20.83%, Cr: 20.83%, Fe: 20.83%, Ni: 20.83%, and Gd: 8.34% to obtain a raw material;
[0059] 2. Wash the raw materials with 10% hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10-3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0060] 3. Melting:
[0061] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min, then adjust to 150kW, melt at 150kW for 5min, then adjust to 200kW, melt at 200kW for 5min, finally adjust to 150kW, melt at 150kW for 15min, and cool down to 100℃ with the furnace;
[0062] ②. Repeat step 3① 3 times. Turn the material upside down between two smeltings. After smelting, pour it to obtain Gd0.4 high entropy alloy, that is, high-strength CoCrFeNi high entropy alloy containing Gd and V.
[0063] Figure 5 Compression curve of the Gd0.4 high entropy alloy prepared in Example 2; Figure 6 This is the IPF diagram of the Gd0.4 high entropy alloy prepared in Example 2. The relevant performance test data are shown in Table 1; Figure 7 This is the polarization curve of the Gd0.4 high entropy alloy prepared in Example 2. The relevant performance test data are shown in Table 2.
[0064] Example 3: A method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V is specifically completed by the following steps:
[0065] 1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.70%, Co: 21.74%, Cr: 21.74%, Fe: 21.74%, Ni: 21.74%, and Gd: 4.34% to obtain a raw material;
[0066] 2. Wash the raw materials with 10% hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0067] 3. Melting:
[0068] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min, then adjust to 150kW, melt at 150kW for 5min, then adjust to 200kW, melt at 200kW for 5min, finally adjust to 150kW, melt at 150kW for 15min, and cool down to 100℃ with the furnace;
[0069] ②. Repeat step 3① 3 times. Turn the material upside down between two smeltings. After smelting, pour it to obtain Gd0.2 high entropy alloy, that is, high-strength CoCrFeNi high entropy alloy containing Gd and V.
[0070] Figure 8 Compression curve of the Gd0.2 high entropy alloy prepared in Example 3; Fig. 9 This is the IPF diagram of the Gd0.2 high entropy alloy prepared in Example 3. The relevant performance test data are shown in Table 1; Fig.10 This is the polarization curve of the Gd0.2 high entropy alloy prepared in Example 3. The relevant performance test data are shown in Table 2.
[0071] Example 4: A method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V is specifically completed by the following steps:
[0072] 1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.89%, Co: 22.22%, Cr: 22.22%, Fe: 22.22%, Ni: 22.22%, and Gd: 2.23% to obtain a raw material;
[0073] 2. Wash the raw materials with 10% hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0074] 3. Melting:
[0075] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min, then adjust to 150kW, melt at 150kW for 5min, then adjust to 200kW, melt at 200kW for 5min, finally adjust to 150kW, melt at 150kW for 15min, and cool down to 100℃ with the furnace;
[0076] ②. Repeat step 3① 3 times. Turn the material upside down between two smeltings. After smelting, pour it to obtain Gd0.1 high entropy alloy, that is, high-strength CoCrFeNi high entropy alloy containing Gd and V.
[0077] Fig.11 Compression curve of the Gd0.1 high entropy alloy prepared in Example 4; Fig.12 This is the IPF diagram of the Gd0.1 high entropy alloy prepared in Example 4. The relevant performance test data are shown in Table 1; Fig.13 This is the polarization curve of the Gd0.1 high entropy alloy prepared in Example 4. The relevant performance test data are shown in Table 2.
[0078] Example 5: A method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V is specifically completed by the following steps:
[0079] 1. Weigh V, Co, Cr, Fe, and Ni metal powders according to the following weight percentages: V: 9.08%, Co: 22.73%, Cr: 22.73%, Fe: 22.73%, and Ni: 22.73% to obtain a raw material;
[0080] 2. Wash the raw materials with 10% hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;
[0081] 3. Melting:
[0082] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min, then adjust to 150kW, melt at 150kW for 5min, then adjust to 200kW, melt at 200kW for 5min, finally adjust to 150kW, melt at 150kW for 15min, and cool down to 100℃ with the furnace;
[0083] ②. Repeat step 3① 3 times. Turn the material upside down between two smeltings. After smelting, pour it to obtain Gd0 high entropy alloy, that is, high-strength CoCrFeNi high entropy alloy containing V.
[0084] Fig.14 Compression curve of the Gd0 high entropy alloy prepared in Example 5; Fig.15 This is the IPF diagram of the Gd0 high entropy alloy prepared in Example 5, and the relevant performance test data are shown in Table 1; Fig.16 This is the polarization curve of the Gd0 high entropy alloy prepared in Example 5. The relevant performance test data are shown in Table 2.
[0085] Table 1 Compressive strain, compressive strength, hardness and average grain size values of various examples
[0086]
[0087] Table 2 Corrosion voltage and corrosion current density of each embodiment
[0088] plan Corrosion voltage(V) <![CDATA[Corrosion current density (μA·cm -2 )]]> Example 1 -0.7093 1.831 Example 2 -0.4802 0.051 Example 3 -0.8873 15.969 Example 4 -0.9921 80.716 Example 5 -0.3755 0.779
Claims
1. A high-strength CoCrFeNi high-entropy alloy containing Gd and V, characterized in that The high-strength CoCrFeNi high-entropy alloy containing Gd and V comprises the following components by weight percentage: V: 8.34%-8.50%, Co: 20.83%-21.28%, Cr: 20.83%-21.28%, Fe: 20.83%-21.28%, Ni: 20.83%-21.28%, and Gd: 6.38%-8.34%.
2. A high-strength CoCrFeNi high-entropy alloy containing Gd and V according to claim 1, characterized in that The high-strength CoCrFeNi high-entropy alloy containing Gd and V includes the following components by weight percentage: V: 8.50%, Co: 21.28%, Cr: 21.28%, Fe: 21.28%, Ni: 21.28%, and Gd: 6.38%.
3. A high-strength CoCrFeNi high-entropy alloy containing Gd and V according to claim 1, characterized in that The high-strength CoCrFeNi high-entropy alloy containing Gd and V includes the following components by weight percentage: V: 8.34%, Co: 20.83%, Cr: 20.83%, Fe: 20.83%, Ni: 20.83%, and Gd: 8.34%.
4. The method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V as claimed in claim 1, characterized in that The preparation method is specifically completed according to the following steps:
1. Weigh V, Co, Cr, Fe, Ni, and Gd metal powders according to the following weight percentages: V: 8.34% to 8.50%, Co: 20.83% to 21.28%, Cr: 20.83% to 21.28%, Fe: 20.83% to 21.28%, Ni: 20.83% to 21.28%, and Gd: 6.38% to 8.34% to obtain a raw material; 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa; The mass fraction of hydrochloric acid described in step 2 is 5% to 20%; 3. Melting: ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min~10min, then adjust to 150kW, melt at 150kW for 5min~10min, then adjust to 200kW, melt at 200kW for 5min~10min, finally adjust to 150kW, melt at 150kW for 10min~15min, and cool down to 100℃~150℃ with the furnace; ② Repeat step 3① 3 to 4 times, turning the material up and down between two smeltings, and pouring after smelting to obtain a high-strength CoCrFeNi high-entropy alloy containing Gd and V.
5. The method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V according to claim 4, characterized in that In step 3①, under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100 kW, melt at 100 kW for 5 min, then adjust to 150 kW, melt at 150 kW for 5 min, then adjust to 200 kW, melt at 200 kW for 5 min, finally adjust to 150 kW, melt at 150 kW for 15 min, and cool down to 100 ° C with the furnace.
6. The method for preparing a high-strength CoCrFeNi high-entropy alloy containing Gd and V according to claim 4, characterized in that In step 3②, repeat step 3① 3 times.
Citation Information
Patent Citations
CrFeCoNiNbx high-entropy alloy and preparation method thereof
CN104674103A